Physical activity and glycosylphosphatidylinositol-specific phospholipase D1 (GPLD1) plasma levels in different age cohorts - Ghulam Shere Raza; Jari Jokelainen; Ville Stenbäck; Nalini Sodum; Toni Karhu; Dominique D. Gagnon; Juhani Leppäluoto; Marjo-Riitta Jarvelin; Sirkka Keinänen-Kiukaanniemi; Karl-Heinz Herzig (PLoS ONE, 2026)
Physical activity (PA) has numerous positive health effects, including improvements in cognitive function. PA stimulates the release of glycosylphosphatidylinositol-specific phospholipase D1 (GPLD1) from the liver, resulting in hippocampal neurogenesis in mice and improved cognition. Interestingly, PA also increases plasma GPLD1 in healthy humans, suggesting a role in cognition, but regulatory factors modulating its concentrations remain unclear. We investigated whether different PA modes, diseases (obesity, hypertension, and diabetes), and age affect plasma GPLD1 levels using three different study cohorts. Plasma GPLD1 levels were analyzed in three studies cohorts comprised of 1) young adults (25 yrs) performing moderate exercise, 2) elderly (68.9 yrs) and 3) of prediabetic subjects (59.4 yrs) performing different habitual PA. We found that prediabetic subjects had higher plasma GPLD1 levels than elderly and young adults. Elderly with diabetes showed significantly higher GPLD1 levels than non-diabetic subjects. In elderly, plasma GPLD1 correlated negatively with average steps, but there was no association after taking their diabetes status into account. GPLD1 exhibited a positive correlation with age in elderly with normal glucose tolerance, and with BMI in subjects with impaired glucose tolerance. Average step numbers negatively correlated with BMI and diastolic BP in the elderly, and BMI in prediabetic subjects. BMI was positively correlated with both diastolic and systolic BP in elderly subjects, and with diastolic BP in young adults. In conclusion age and diabetes affect plasma GPLD1 levels in humans. Age is one of the determining factors, as moderate exercise in young adults did not change plasma GPLD1 levels. Habitual physical activity did not alter plasma GPLD1 levels in individuals with prediabetes or diabetes. The release of GPLD1 into the blood and its mechanistic influences on cognitive functions would need further investigation in humans.